RAFT: An IoT-Based Nutrition Monitoring System for Bok Choy Hydroponics Plants - Himawan, Aldi; Putra, Widhy Hayuhardhika Nugraha; Setiawan, Eko (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
The Internet of Things (IoT) plays a crucial role in technology advancements, especially in the agricultural sector, such as hydroponics. Manual monitoring of parameters such as nutrient levels, pH, and water levels in plants consumes farmers' time and energy and increases the risk of crop failure. This research aims to evaluate the effectiveness of using IoT RAFT (Remote Automated Farming Technology) system for farmers, particularly hydroponic bok choy farmers, to monitor and control plant nutrient levels and the development process using waterfall as a research methodology. The parameters tested in this research include the height of the bok choy, the number of leaves, and the weight of the harvest of the bok choy. We conducted this research on 14 plants for one harvest period, then we used linear regression to determine the growth rate by calculating the slope. The results show that the plant height, the number of leaves, and the harvest weight using the IoT RAFT system are 0.5897 cm/day, 0.6391 leaves/day, and 216.43 grams, respectively. We also compared the IoT RAFT system with a non-IoT bok choy growing method, and we concluded that our IoT RAFT system has a better growth rate compared to the non-IoT bok choy growing method.